Clinical risk score for prediction of early left ventricular thrombus after percutaneous coronary intervention for ST-elevation myocardial infarction. (25th November 2020) - Reinstadler, S; Holzknecht, M; Reindl, M; Tiller, C; Lechner, I; Mayr, A; Brenner, C; Klug, G; Bauer, A; Metzler, B
Abstract: Background: Cardiac magnetic resonance (CMR) is the reference standard for left ventricular (LV) thrombus detection in patients with acute ST-elevation myocardial infarction (STEMI). However, routine CMR imaging is currently not recommended post-STEMI. Objective: This observational study sought to develop a practical risk score for the prediction of early LV thrombus formation after STEMI to identify patients in whom routine CMR might be appropriate. Methods and results: Five hundred and fifty-six consecutive patients underwent transthoracic echocardiography (TTE) and CMR at 3 [IQR: 2–4] days after primary percutaneous coronary intervention (PCI) for acute STEMI. A LV thrombus was visualized in 12 patients (2.2%) using TTE and in 22 patients (4%) using CMR. A weighted risk score including multivariable associates of LV thrombus formation (LV ejection fraction by TTE, peak high-sensitivity cardiac troponin T and peak high-sensitivity C-reactive protein) and left anterior descending coronary artery as culprit vessel, with a range of 0 to 7 points (median risk score: 2 points) showed a strong and significantly higher area under the curve (0.93 (95% CI 0.88–0.97; p<0.001)) for LV thrombus prediction than each individual risk factor alone (p<0.001). The sensitivity and the specificity of the risk score was 91% and 80%, respectively. The incidence of LV thrombi was 0% in the very low risk group (0 to 1 points, n=248), 1.8% in the low risk group (2 to 4 points, n=219) and 20.2% in the high risk group (5 to 7 points, n=89). Eighty-two percent of all LV thrombi occurred in the high risk group (number needed to scan to detect one LV thrombus=5). Conclusions: The proposed risk score provides incremental value for the prediction of early LV thrombus and could be useful to identify STEMI patients in whom routine CMR for LV thrombus evaluation could be most meaningful. Additional investigation is warranted to validate the clinical application of the score. Funding Acknowledgement: Type of funding source: None